2021
DOI: 10.1007/s42452-021-04461-3
|View full text |Cite
|
Sign up to set email alerts
|

Nanoparticles used as an ingredient in different types of concrete

Abstract: Attempts to modify cement-based mixtures and to improve their properties have always attracted the attention of researchers. Favorable effects of nanoparticles, such as small particle size, high reactivity, and great surface area, have made them be used as one of the best replacements of cement. This paper aims to review the previous researches conducted regarding the effects of nanoparticles on the properties of concretes. Influence of various types of nanoparticles on the workability of fresh composite, mech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(4 citation statements)
references
References 67 publications
0
2
0
Order By: Relevance
“…The incorporation of nanoclay into concrete has several beneficial effects, including reducing building energy consumption, enhancing thermal insulation properties, improving thermal stability, fire resistance, thermal performance, behavior, resistance to cracking and degradation, and decreasing thermal conductivity, which leads to effective insulation and lower energy consumption during heating and cooling periods [33]. Nanoparticles contribute to the development of strength in cement-based materials by enhancing the hydration process of cement, resulting in the formation of calciumsilica-hydrate (C-S-H) and improved overall strength [99].…”
Section: Nanoclays In Concrete and Asphalt Bindersmentioning
confidence: 99%
“…The incorporation of nanoclay into concrete has several beneficial effects, including reducing building energy consumption, enhancing thermal insulation properties, improving thermal stability, fire resistance, thermal performance, behavior, resistance to cracking and degradation, and decreasing thermal conductivity, which leads to effective insulation and lower energy consumption during heating and cooling periods [33]. Nanoparticles contribute to the development of strength in cement-based materials by enhancing the hydration process of cement, resulting in the formation of calciumsilica-hydrate (C-S-H) and improved overall strength [99].…”
Section: Nanoclays In Concrete and Asphalt Bindersmentioning
confidence: 99%
“…Nanoparticles have been shown to improve the microstructure of concretes by filling the pores within the cement to increase its packing level, providing increased mechanics as the nanoparticle percentage increases. [65,66] William and coworkers similarly found that compressive strength in explanted vertebral bodies treated with PMMA and PMMA supplemented with HA decreased in groups treated with the 1g:3g (PMMA:HA) group compared to the 1g:1g and 1g:2g groups. [67] While the compressive mechanics of mPOC-40HA are promising, additional tensile testing would need to be evaluated as increasing HA concentration has been shown to decrease tensile and bending characteristics.…”
Section: 2mentioning
confidence: 99%
“…Nanotechnology is also used for design and construction processes. Nanotechnology will enhance existing construction materials and generate products with their properties (Mahmood and Kockal, 2021). Different structural materials, for instance, with special qualities like lighter, stronger compounds, fire insulators, sound absorbers, low maintenance coatings, nanoscale sensors, solar cells, etc., Polymers, metals, pottery, compounds, and semiconductor materials are different categories of material science.…”
Section: Introductionmentioning
confidence: 99%